Involvement of non-verbal communication in the tactics of Football game - Ana Gertrudis Palacios-Aldana; Enrique Iznaga-Bouly; Inalvis Mengana-Osorio (Universidad de Guantánamo, 2019)
The work deals a category, which is often undervalued its role for the success of the game of football and therefore for the implementation of tactics. Arguments are presented to understand the importance of communication as a social phenomenon within this context. The arguments on the subject are completed with examples of the implication of non-verbal communication from different channels in the development of the reference game.